An Investigation on Sentiment Analysis - Ledalla, Sukanya; Mahalakshmi, Tummala Sita (International Journal of Computer Sciences and Engineering, 2025)
Sentiment analysis is useful for multiple tasks including customer satisfaction metrics, identifying market trends for any industry or products, analyzing reviews from social media comments. These kinds of data assets, which are a broad stage of people's sentiment, suggestions, input, and audits, are viewed as intense witnesses and have become a valuable resource for big industries, research and technology markets, news service providers, and numerous domains where sentiment analysis became a useful tool. This paper discusses on deep learning algorithms applied in recent years for sentiment analysis. The main goal of this paper is to analyze how deep learning research is growing in different application areas and can be helpful for sentiment analysis